2003
DOI: 10.1007/bf03017853
|View full text |Cite
|
Sign up to set email alerts
|

Increased body mass indexper se is not a predictor of difficult laryngoscopy

Abstract: P Pu ur rp po os se e: : We investigated the association between morbid obesity and difficult laryngoscopy (DL). M Me et th ho od ds s: :In a prospective, controlled study we evaluated the impact of different variables on the prediction of DL in 200 morbidly obese (study group-SG), and 1,272 non-obese (control group-CG) patients undergoing elective surgery. Variables assessed included age, sex, body mass index (BMI), protruding, loose, and missing upper teeth, thyro-mental distance, temporo-mandibular joint (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
7
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 19 publications
7
86
7
2
Order By: Relevance
“…This result confirms the conclusions of a Canadian study [19] of intubation in the supine position. The authors found that increasing age led to an increase in the Cormack and Lehane grade but that increasing BMI did not.…”
Section: Discussionsupporting
confidence: 91%
“…This result confirms the conclusions of a Canadian study [19] of intubation in the supine position. The authors found that increasing age led to an increase in the Cormack and Lehane grade but that increasing BMI did not.…”
Section: Discussionsupporting
confidence: 91%
“…OSA has been clearly associated with difficult intubation. 9,12,13 This is also the case in the present study, where all the patients with OSA had difficult (grade III) laryngoscopy views.…”
Section: Discussionsupporting
confidence: 79%
“…5 Intraoperative problems during bariatric surgery include but are not limited to airway management challenges (ie Anesthesia for bariatric surgery T Ezri et al difficult intubation), difficulties in ventilating the patients' lungs, problems related to laparoscopy and anesthesia (hypoxemia, hypercarbia, cardiovascular complications, pulmonary aspiration of gastric contents, etc) and surgical complications (conversion to open procedure, bleeding, organ perforation, etc). The magnitude of the BMI and obesity per se may 7,8 or may not 9,10 contribute to the airway management difficulty in these patients. This controversy may be explained by different patterns of body fat distribution.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In a cohort of 91,332 consecutive patients, a BMI [ 35 kgÁm 2 was found to be a statistically significant predictor of difficult and failed intubation. 19 Conversely, Erzi et al found that BMI was not an independent predictor of direct laryngoscopy view; 20 however, in this study, the combination of BMI and abnormal upper teeth was a significant predictor of difficult laryngoscopy. 20 By using ultrasound to quantify anterior neck soft tissue at the level of the vocal cords, Erzi et al observed that morbidly obese patients in whom difficult laryngoscopy was encountered had more pre-tracheal soft tissue and a greater neck circumference than patients who experienced an uncomplicated laryngoscopy; pre-tracheal soft tissue thickness was [mean (SD)] 28 (2.7) mm vs 17.5 (1.8) mm, respectively (P \ 0.001) and neck circumference was 50 (3.8) cm vs 43.5 (2.2) cm, respectively (P \ 0.001).…”
Section: Direct Laryngoscopy and Intubationcontrasting
confidence: 55%
“…19 Conversely, Erzi et al found that BMI was not an independent predictor of direct laryngoscopy view; 20 however, in this study, the combination of BMI and abnormal upper teeth was a significant predictor of difficult laryngoscopy. 20 By using ultrasound to quantify anterior neck soft tissue at the level of the vocal cords, Erzi et al observed that morbidly obese patients in whom difficult laryngoscopy was encountered had more pre-tracheal soft tissue and a greater neck circumference than patients who experienced an uncomplicated laryngoscopy; pre-tracheal soft tissue thickness was [mean (SD)] 28 (2.7) mm vs 17.5 (1.8) mm, respectively (P \ 0.001) and neck circumference was 50 (3.8) cm vs 43.5 (2.2) cm, respectively (P \ 0.001). 21 Komatsu et al did not find increased pre-tracheal tissue to be a good predictor of difficult laryngoscopy in obese patients; 22 however, the patients in this study had a comparatively smaller neck circumference [43.5 (4.7) cm vs 44.3 (5.3) cm; P \ 0.5] in the difficult and easy laryngoscopy groups, respectively.…”
Section: Direct Laryngoscopy and Intubationcontrasting
confidence: 55%